Challengges Faced By Pre-Service English Teachers: Designing Lesson Plans For The Merdeka Curriculum: - Masrini Masrini; Nila Kencana; Yuneva Yuneva (Multidisciplinary Journals, 2026)
The aims of this research are to know what the challenges faced by pre-services teachers to designing lesson plan for the merdeka curriculum at SMPN 23 South Bengkulu: knowing the challenges faced by pre-service teachers in designing the lesson plan merdeka curriculum in English language learning. This research method uses a qualitatative approach with data collection techniques in the form of observation, interviews and documentation as well as data analysis technique in the form of organizing and familiarizing, coding and reducing and interpreting and representings. The result of this research fount that: first, this study reveal several challenges encountered by pre-service teachers in designing Lesson Plans (RPP) aligned with the Merdeka Curriculum. One major challenge lies in assessment practices, as many students still receive low scores, resulting in the failure to meet intended learning objectives. Second, the researcher is that the majority of students can understand the material given by the teacher based on the existing lesson plan, but there are some students who still do not understand some parts of the learning process. This is what causes several meetings that may cause a mismatch between the lesson plan and the material to be delivered at several meetings.